The dynamic myeloid-enriched microenvironment of glioblastoma: a major challenge to immunotherapy efficacy - Lamorlette, Cindy; Boura, Cédric; Pinel, Sophie; Bensoussan, Danièle; Dotti, Gianpietro; Alanio, Cécile; Reppel, Loïc (Frontiers in Immunology, 2026)
Glioblastoma (GBM) is the most common and aggressive brain tumor in adults, and current treatments remain poorly efficient. In this context, immunotherapies may represent promising strategies. However, their efficacy is often limited by a strong negative impact of the tumor microenvironment (TME) of glioblastoma. Several factors such as tumor cells mutational profile, previous lines of conventional treatments, or biological factors, have been shown as involved in TME modulation. In this review, our goal is to give an overview of the main modulating factors of the TME of glioblastoma tumors. We will also highlight the importance of developing complex and integrative models to study this microenvironment. At the end, by highlighting critical components of the glioblastoma microenvironment, this review aims to support the development of next-generation, more effective and personalized immunotherapeutic strategies.